Oscillations in Prandtl slope flow started from rest. (27th December 2016) - Fedorovich, E.; Shapiro, A.
Abstract : We study oscillations that develop in flows along a uniform planar slope in an initially resting stratified fluid as a result of sudden application of a surface buoyancy flux. After an oscillatory adjustment (transition), the fluid reaches another steady state that corresponds to a stationary slope flow. The analysis is focused on the temporal evolution of the integral momentum and buoyancy structure in the laminar Prandtl‐type slope flow. The main questions addressed are related to physical conditions leading to emerging of the en masse oscillations in the transitioning slope flow, the frequency of these oscillations, and features of their temporal evolution. The persistence of oscillations in Prandtl‐type slope flows is found to be associated, somewhat paradoxically, with the fast temporal decay of the surface stress oscillations in the process of the stress approaching a constant value. This relatively rapid evolution of the surface stress progressively weakens damping of the integral momentum and buoyancy oscillations. Extensions of the analyses to the Prandtl slope flow driven by the surface buoyancy and to the turbulent slope flows are proposed and discussed.